THE ORIGIN AND DEVELOPMENT OF PAINTING IN UZBEKISTAN (International journal of artificial intelligence, 2025)
This article covers the processes of the origin and formation of the history of painting in Uzbekistan. The rich cultural heritage of Uzbekistan, its geographical and historical features played an important role in the development of painting. The article analyzes the formation of painting in ancient times, in particular, through applied art and religious images. The interaction between major cultural centers in Uzbekistan, as well as different peoples and their fine arts, created unique styles of painting. The article examines the most important stages in the history of painting in Uzbekistan, and also draws attention to the place of this area in modern art.